A liquid crystal derived from ruthenium(II,III) and a long-chain carboxylate - Zelcer, Andrés (2002)
The title compound, catena-poly[[tetrakis(μ-decanoato-κ2O:O′)diruthenium(II,III)(Ru—Ru)]-μ-octanesulfonato-κ2O:O′], [Ru2(C10H19O2)4(C8H17O3S)], is an octanesulfonate derivative of the mixed-valence complex diruthenium tetradecanoate. The equatorial carboxylate ligands are bidentate, bridging two Ru atoms to form a dinuclear structure. Each of the two independent dinuclear metal complexes in the asymmetric unit is located at an inversion centre. The octanesulfonate anion bridges the two dinuclear units through axial coordination. The alkyl chains of the carboxylate and sulfonate ligands are arranged in a parallel manner. The global structure can be seen as infinite chains of polar moieties separated by a double layer of non-polar alkyl groups, without interdigitation of the alkyl chains.